A critical review of literature on "unplugged" pedagogies in K-12 computer science and computational thinking education. Issue 1 (2nd January 2021) - Huang, Wendy; Looi, Chee-Kit
ABSTRACT: Background and Context: Computational thinking (CT) is considered as a valuable literacy for all students, and its inclusion in compulsory schooling could increase the numbers of underrepresented students who pursue computing-related careers. Computer Science Unplugged (CSU) had success in making computer science (CS) accessible to K–12 students in outreach settings. Such "unplugged" approaches have the potential to do the same in formal education. Objective: This review considers how research findings on unplugged pedagogies might advance CS/CT education priorities, while highlighting areas of unknown and tension. Method: We conducted a search in academic databases using terms +unplugged "computer science" and +unplugged CT, and related terms. Findings: We synthesized our review with existing ones to inform the priorities of CS-for-all and CT development. We surfaced CSU's limitations to broaden access for underrepresented students and suggested a remedy. We proposed 10 research questions that fill key gaps to support efforts that provide just access to quality CS/CT education.